The Impact Of Tiket.Com Website Quality And E-Trust On Concert Ticket Purchasing Decision: Pengaruh Kualitas Website Tiket.Com Dan E-Trust Terhadap Keputusan Pembelian Tiket Konser - Wahyuni , Risma Ika; Purwanto, Nuri (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative research aims to investigate the influence of Website Quality and E-Trust on the purchasing decisions of concert tickets among EXO fans using Tiket.com services. Employing a descriptive research method, data was collected from 100 respondents through purposive sampling and analyzed using SPSS. The study revealed that both Website Quality and E-Trust significantly affect the concert ticket purchase decisions of EXO fans. These findings contribute to the understanding of online consumer behavior and hold implications for ticket reservation services, emphasizing the importance of attractive, easily accessible websites and robust online trust mechanisms to foster positive purchase decisions. Highlights: Significance of Website Quality: The study examines the impact of website quality on purchase decisions, emphasizing the need for an attractive and user-friendly online platform to enhance customer engagement and conversion rates. Crucial Role of E-Trust: The research highlights the pivotal role of online trust in influencing consumers' decisions to purchase concert tickets online, underlining the importance of establishing secure and reliable platforms. Insights into EXO Fans' Behavior: The study provides valuable insights into the behavior of EXO fans as they engage with ticket reservation services, aiding businesses in catering to the preferences of this specific target audience. Keywords: Website Quality, E-Trust, Purchase Decision, Concert Tickets, EXO Fans